Co‐Agent Assisted Peroxide Vulcanization of Halogen‐Free Flame Retardant EPDM Compounds for Cable Sheathing - Gül, Gürcan; Gözlü, Cem; Öncel, Şehriban; Karaağaç, Bağdagül (Macromolecular symposia., 2025)
ABSTRACT Thanks to advancements in technology and industry, expectations from polymer compounds are rising day by day. During a fire, flame retardancy and self‐extinguishing properties are expected from polymer compounds in various industrial applications. Even though halogen‐containing polymers are flame resistant, they release toxic and corrosive gases when burned, which limits their use. For this reason, a number of studies on halogen‐free flame retardant (HFFR) compounds have been performed to improve material performance. Ethylene propylene diene rubber (EPDM) is widely used as a cable insulation material due to its superior dielectric properties and weathering resistance. However, EPDM is highly flammable when used alone. This issue can be overcome by incorporating various flame‐retardant additives. In this study, the effects of two types of peroxides, four types of co‐agents, and intumescent flame retardants (IFRs) on the rheological, physical, mechanical, thermal aging, and flammability properties of EPDM‐based rubber formulations were investigated. Dicumyl peroxide (DCP) and di(tert‐butyl peroxyisopropyl) benzene (BIBP) were selected as the peroxides. Triallyl isocyanurate (TAIC), high vinyl 1,2‐polybutadiene (HVPBD), trimethylol propion trimethacrylate (TMPTMA), and zinc dimethacrylate (ZDMA) were used as co‐agents. Additionally, an IFR system consisting of ammonium polyphosphate (APP), pentaerythritol (PER), and expanded graphite (EG) was used in the 2 phr co‐agent‐containing compounds. The IFRs provided a good level of flame retardancy, along with mechanical properties comparable to those of the peroxide‐cured EPDM compounds. In conclusion, BIBP and ZDMA were found to be the most effective curing system for the EPDM‐based HFFR compounds prepared in this study.